The impact of foreign direct investment on stock market growth: Evidence from Pakistan - Al-Delawi, Amjad S; Shah, Sayyed Sadaqat Hussain; Harjan, Sinan Abdullah; Karim, Fazal; Mehran, Muhammad; Ahmad, Sohail (International Journal of Management and Sustainability, 2023)
This paper aims to investigate the impact of foreign direct investment (FDI) on stock market growth in Pakistan from 1990 to 2020. The study aims to evaluate the impact of FDI on stock market growth in both the short and long term, as well as examine the impact of economic growth on stock market growth. The study uses an Autoregressive Distributed Lag (ARDL) model to analyze the long-term impacts of FDI on the stock market and an Error Correction Model (ECM) to evaluate the short-term impact. The study reveals a substantively significant and positive influence of Foreign Direct Investment (FDI) on the growth of the stock market, observed from both a short-term and long-term perspective. Gross National Income (GNI) and Exchange Rate (ER) also have a significant bearing on stock market growth, while Interest Rate (IR) is found to have a negative impact but is statistically insignificant. The findings also confirm the impact of economic growth on stock market development, establishing a triangular relationship between FDI, Economic Growth, and Stock Market Growth. The study concludes that FDI has a significant positive impact on stock market growth in Pakistan in both the short and long term. It further suggests that macroeconomic policies should be developed and a tax-free market environment should be created to stimulate and encourage foreign direct investment for economic growth and stock market growth. The study’s policy implications suggest that government officials should implement viable macroeconomic policies and create a tax-free market environment to encourage foreign direct investment for economic and stock market growth in Pakistan.